Discovery Learning–Based Worksheets Integrating Flood Disaster Literacy to Enhance Collaboration and Creativity in Elementary School - Agus Arman; Irwan Said; Nurjannah; Supriyatman; Muslimin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
Science learning on the topic of ecosystems in elementary schools still faces various problems, such as low student engagement, limited contextual teaching materials, and less than optimal development of collaboration and creativity skills. The flood-prone environment of students demands learning that integrates disaster literacy with ecosystem concepts through active and meaningful activities. This study aims to analyze the effectiveness of Student Worksheets (LKPD) based on the Discovery Learning model containing flood disaster literacy on the topic of ecosystems in improving collaboration and creativity skills of elementary school students. This study is a research and development (R&D) using the ADDIE model. The research subjects consisted of fifth-grade students selected using purposive sampling techniques. Data were collected through expert validation, observation, testing, and documentation, then analyzed using validity analysis techniques and analysis of learning outcomes improvement. The results showed that the developed LKPD obtained the category of very valid and very practical based on the results of the validator's assessment and student responses to use. The implementation of LKPD also showed effectiveness in improving collaboration and creativity skills of students who were in the high category. Thus, the Discovery Learning-based LKPD containing flood disaster literacy on the topic of ecosystems is declared valid, practical, and effective for use in science learning in elementary schools to improve students' collaboration and creativity skills.